Increasing student knowledge with counseling on anticipating earthquakes - Anri Noor Annisa Ramadan; Agi Rivi Hendardi; Novi Asniar; Dicky Nurmayadi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
West Java experienced 522 earthquake events, of which 93 occurred in Tasikmalaya City and Regency. This has made a lot of noise in the community and created excessive concern, so the community needs to be educated, especially in terms of preparedness in dealing with earthquake disasters in order to prevent more severe impacts. Elementary school education is the first door to introduce students to disaster preparedness and mitigation. One of the elementary schools that does not have non-structural mitigation efforts is Cihideungbalong Islamic Elementary School. The location, which is in a densely populated area, is also vulnerable to the effects of earthquake disasters, so it is necessary to have an earthquake anticipation evacuation route and counseling in the Cihideungbalong Islamic Elementary School environment. The method used is socialization about earthquake anticipation and simulation assistance after an earthquake by following the evacuation route. Increasing students' knowledge of the earthquake, which consists of knowledge about the dangers of the earthquake, making support tools and evacuation routes for earthquake anticipation. The results of this activity have increased student preparedness, from an increase of 17 percent for student knowledge of how the earthquake occurs, 33 percent regarding student calmness in facing the earthquake, 56 percent for self-rescue during an earthquake, and 78 percent for accuracy/skill of students in simulating self-rescue through the earthquake evacuation route.Â